THE EFFECT OF BURNOUT ON JOB SATISFACTION MEDIATED BY WORK LIFE BALANCE AT BANK PEREKONOMIAN RAKYAT GIANYAR PARTHASEDANA - Gusti Ayu Diva Kartika Sari; Ayu Desi Indrawati (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Burnout is a condition of physical and emotional exhaustion experienced by employees due to prolonged work pressure and has the potential to reduce job satisfaction. In the context of banking organizations, high job demands, excessive workloads, and limited time between work and personal life are factors that may trigger burnout. Therefore, this study aims to analyze the effect of burnout on job satisfaction with work–life balance as a mediating variable among employees of Bank Perekonomian Rakyat Gianyar Parthasedana. This study employed a quantitative approach with an associative research design. The survey method was conducted by distributing questionnaires to all permanent employees of BPR Parthasedana, totaling forty respondents; therefore, the sampling technique used was the census method. Data were analyzed using path analysis to examine both direct and indirect relationships between variables, and the Sobel test was applied to assess the mediating role of work–life balance. Prior to the analysis, classical assumption tests were conducted, including normality, multicollinearity, and heteroscedasticity tests. The results indicate that burnout has a negative and significant effect on job satisfaction. Burnout also has a significant negative effect on work–life balance, while work–life balance has a significant positive effect on job satisfaction. The Sobel test results demonstrate that work–life balance mediates the relationship between burnout and job satisfaction. These findings suggest that higher levels of burnout experienced by employees reduce work–life balance and consequently lead to lower job satisfaction. Practically, this study provides insights for the management of BPR Parthasedana to pay greater attention to employees’ work–life balance as an effort to reduce burnout and sustainably improve job satisfaction. The findings are expected to serve as a basis for developing effective and sustainable human resource policies.